2010
DOI: 10.1093/nar/gkq1192
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear mRNA quality control in yeast is mediated by Nrd1 co-transcriptional recruitment, as revealed by the targeting of Rho-induced aberrant transcripts

Abstract: The production of mature export-competent transcripts is under the surveillance of quality control steps where aberrant mRNP molecules resulting from inappropriate or inefficient processing and packaging reactions are subject to exosome-mediated degradation. Previously, we have shown that the heterologous expression of bacterial Rho factor in yeast interferes in normal mRNP biogenesis leading to the production of full-length yet aberrant transcripts that are degraded by the nuclear exosome with ensuing growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 54 publications
3
44
0
Order By: Relevance
“…In our previous studies, we monitored the effect of Rho activity by measuring the steady-state levels of a set of widely-studied yeast mRNAs (PMA1, PGK1, FBA1 and ACT1) and we found that PMA1 was the most affected with a 60% to 70% reduction, which led us to use it as a model transcript for further characterization of the QC system. 15,16 As shown by Northern blot analysis and RT-qPCR quantifications in Fig. 1, a large drop in the level of PMA1 mRNA is observed under Rho inducing conditions and the absence of the exonuclease Rrp6p in the rrp6D strain restores the PMA1 mRNA to nearly normal level.…”
Section: Hxk1 Transcript Is Affected By Rho Activity Independently Ofmentioning
confidence: 80%
See 4 more Smart Citations
“…In our previous studies, we monitored the effect of Rho activity by measuring the steady-state levels of a set of widely-studied yeast mRNAs (PMA1, PGK1, FBA1 and ACT1) and we found that PMA1 was the most affected with a 60% to 70% reduction, which led us to use it as a model transcript for further characterization of the QC system. 15,16 As shown by Northern blot analysis and RT-qPCR quantifications in Fig. 1, a large drop in the level of PMA1 mRNA is observed under Rho inducing conditions and the absence of the exonuclease Rrp6p in the rrp6D strain restores the PMA1 mRNA to nearly normal level.…”
Section: Hxk1 Transcript Is Affected By Rho Activity Independently Ofmentioning
confidence: 80%
“…Our previous analyses by the Rho-based approach of a subset of commonly-studied yeast transcripts such as PMA1 and PGK1 substantiated the essential role of Rrp6p in the elimination of aberrant mRNPs and revealed the implication of Nrd1p-Nab3p complex in the activation of the QC process. [15][16][17] However, in the course of those studies we noticed that the HXK1 transcript, which is also strongly affected by Rho action, was not rescued from degradation upon alteration of the Nrd1p-Nab3p complex or removal of Rrp6p and its activating cofactors. In the present work, we show that the elimination of Rho-induced aberrant HXK1 mRNPs is in fact mediated by an alternative nuclear QC pathway that relies on the degradation activity of the 5 0 -3 0 exonuclease Rat1p.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations